Kant y Nancy: «beyond the idea»: Annotations about the phenomenological reception of the problem of freedom - Quintana Montes, Jorge Luis (Pensamiento. Revista de Investigación e Información Filosófica, 2022)
The purpose of this paper is show —from the considerations of Nancy and Kant— the way in which freedom can only be thought of in its full radicality, when it is assumed from a historical key. Although Nancy criticizes Kant for the identification of Idea and Freedom, he acknowledges in the Königsberg philosopher to have visualized a «beyond the idea». The «beyond», according to Nancy, is placed by Kant simply in the objective reality of the idea of freedom. In our view, said «beyond the idea» is embedded and nourished by Kantian historical and legal reflections. This fact allows us to create a common ground for dialogue between the Kantian and the phenomenological position: freedom and history constitute an indissoluble unity.